Mengelola dan Meningkatkan Mutu Pembelajaran Pendidik dan Tenaga Kependidikan dalam Manajemen Lembaga Pendidikan Islam - Amiruddin Siahaan; Rizki Akmalia; Lydia Amelia; Ahmad Ardhi Mauluddin Sitorus; Muhammad Syaukani Siraj; Yusril Ardiansyah (Departement of Mathematics Education, 2023)
This research to explain the topic of managing and improving the learning quality of educators and education staff in an Islamic education institution management. This research was conducted using a qualitative-descriptive method. The results of the research show that there are categories or stages in the management of education management and educational staff, namely; (1) Coaching and Development, (2) Promotion and Transfer, (3) Dismissal, (4) Compensation, and (5) Assessment. In improving the quality of learning, teachers as educators have a very important position and strategy in developing the potential of students. In the teacher is the glory and safety of the nation's future by instilling the basic values ​​of the ancestors as the ideals of National Education in forming a person who is physically and mentally prosperous. To increase the professionalism of educators in learning, it is improved through ways of attending upgrading, attending educational courses. conducting visits to other schools or comparative studies, increasing reading, establishing relationships with student guardians, increasing the use of methods, improving materials, as well as improving facilities and infrastructure.